Metaphor and the ancient novel - Harrison, S. J.; Paschalis, Michael; Frangoulidis, Stavros A. (Ancient narrative. Supplementum, 2005)
This thematic fourth Supplementum to Ancient Narrative, entitled Metaphor and the Ancient Novel, is a collection of revised versions of papers originally read at the Second Rethymnon International Conference on the Ancient Novel (RICAN 2) under the same title, held at the University of Crete, Rethymnon, on May 19-20, 2003. Though research into metaphor has reached staggering proportions over the past twenty-five years, this is the first volume dedicated entirely to the subject of metaphor in relation to the ancient novel. Not every contributor takes into account theoretical discussions of metap.